To solve the equation \( 5x - 12 - 6x = -10x + 7 - 1 \), follow these steps:
-
Combine like terms on both sides of the equation.
On the left side:
\( 5x - 6x = -x \), so the left side becomes: \[ -x - 12 \]On the right side:
\( 7 - 1 = 6 \), so the right side becomes: \[ -10x + 6 \]The equation now looks like this: \[ -x - 12 = -10x + 6 \]
-
Add \( 10x \) to both sides to get all the \( x \) terms on one side.
\[ -x + 10x - 12 = 6 \]
This simplifies to: \[ 9x - 12 = 6 \] -
Add \( 12 \) to both sides to isolate the \( x \) term.
\[ 9x - 12 + 12 = 6 + 12 \]
This simplifies to: \[ 9x = 18 \] -
Divide both sides by \( 9 \) to solve for \( x \).
\[ x = \frac{18}{9} \]
This simplifies to: \[ x = 2 \]
So, \( x = 2 \) is the solution to the equation \( 5x−12−6x=−10x+7−1 \).